Thiosemicarbazone- and Thiourea-Functionalized Calix[4]arenes in cone and 1,3-alternate Conformations: Receptors for the Recognition of Ions - Andrés Ochoa; Belén Hernández-Arancibia; José Herrera-Muñoz; Horacio Gómez-Machuca; Claudio Saitz (Chemosensors)
In this research we have synthesized and evaluated five calix[4]arene-based receptors functionalized with thiosemicarbazone or thiourea groups, incorporating pyridinyl naphthalene or triazolopyridine chromophores in 1,3-alternate, pinched cone and cone conformations. The ion recognition capabilities of these receptors were investigated using UV-visible and fluorescence spectroscopy. Receptor (I), which adopts a pinched cone conformation with thiosemicarbazone groups, demonstrated bifunctional sensing abilities by detecting both cations and anions. Receptors (II) and (III) showed remarkable selectivity and sensitivity for Cu2+ ions. Receptors (IV) and (V), in cone and 1,3-alternate conformations, respectively, where functionalized with a triazolo[1,5-a]pyridine fluorophore and exhibited highly sensitive ON-OFF fluorescence sensing for Co2+, Cu2+ and Ni2+ ions, with significant fluorescence quenching upon binding and a low detection limit of 2.94 µg/L for the Co2+ ion in receptor (IV). Ion receptor (I) demonstrates a strong performance in broad-spectrum ion detection, whereas the structural conformations of receptors (IV) and (V) play a pivotal role in their remarkable selectivity and sensitivity for specific transition metals in fluorescence-based sensing.